Self-assembly, interlocking, interconversion and anion-binding catalysis in phenoxazine-based Pd2L4 and Pd4L8 coordination cages - Qiong-Yan Hong; Bin Huang; Meng-Xiang Wu; Jun-Yao Jiang; Hai-Bo Yang; Xiao-Li Zhao; Guido H. Clever; Xueliang Shi (Nature Communications)
Abstract Interpenetration is a phenomenon frequently encountered in self-assembled Pd2L4-type coordination cages, while the mechanism of the interpenetration process remains unclear. Here we show the synthesis and solvent-mediated interconversion of highly soluble phenoxazine-based monomeric cage 1 and corresponding interlocked dimer 2. We succeed in the isolation and single-crystal structure analysis of both 1 and 2 with the same guest anion by changing the solvents utilized in self-assembly. The monomeric-to-dimeric cage conversion occurs by heating in weakly coordinating solvents, while dimeric-to-monomeric cage conversion takes place through a disassembly and reassembly process in strongly coordinating solvents at low concentration or by the addition/removal of competing ligand. The interconversion may be driven by the distinct thermodynamic stabilities of 1 and 2 in different solvents. Additionally, Cl– anions template the interpenetration of 1 because of the strong chloride binding affinity of 2 which could serve as an anion-binding catalyst for the C–Cl bond cleavage.